(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Praja RN, Edila R, Yudhana A, Saputro AL, Hamonangan JM, Praja SS. 2024. Short Communication: Investigation of mecA-positive and Methicillin-Resistant Staphylococcus aureus (MRSA) in dairy goat with subclinical mastitis from traditional farms in Banyuwangi, Indonesia. Biodiversitas 25: 1638-1643. Raw milk has the potential to transmit bacteria resistant to antibiotics and serve as a medium for the development of food-borne illnesses. Staphylococcus aureus is a harmful bacterium that can infect host cells and carry antibiotic-resistant genes. This study aims to investigate the occurrence of Methicillin-Resistant Staphylococcus aureus (MRSA) which contains mecA coding gene from raw goat milk in Banyuwangi, East Java, Indonesia. 150 raw milk samples were collected from five goat farms in Banyuwangi, East Java, Indonesia. S. aureus was isolated using selective media, and antibiotic susceptibility testing was conducted using the Mueller-Hinton agar diffusion method. MRSA was confirmed using the oxacillin and cefotaxime resistance screen agar test, with the presence of mecA genes identified through polymerase chain reaction. The results show that the prevalence of S. aureus was 30.6%. Of the 46 S. aureus isolates, 28 (60.87%) were categorized as MRSA. The mecA gene was observed in 9 (32.14%) MRSA isolates. The presence of MRSA in raw goat milk poses a significant public health threat, as bacteria carrying the mecA gene for antimicrobial resistance can spread through animal products like raw milk. Enhanced hygiene and sanitation protocols in dairy goat farms are essential prevention measures that must be strictly implemented.